Development and validation of an ‘intention to stay’ scale for medical academics in Public Universities in Malaysia - Ismail, Wan Ismahanini (2018)
There are few prominent scales that are normally being used by researchers to measure intention to stay or leave. Most scales use limited number of items, and some other measures are lacking in information on metric properties. There is lack of scale tailored to the needs of medical academics’ mission and able to measure their intentions level towards staying or leaving the university. In contrast to previous studies that were using theory or model that did not explain the formation of intention, this study employs dimensions of feelings, beliefs and desires based on the integration of Belief-Desire-Intention (BDI) Model and Integrated Behavioural Model (IBM). Moreover, there was a significant increase of employing Rasch model as compared to Classical Test Theory (CTT) which is normally used in the social sciences for quantifying and assessing psychological construct and personality evaluation. Rasch models have been demonstrated to be better over CTT in the construction of variable and validation. Although a significant number of articles have been published on intention to stay, there is a shortage of investigators using a systematic approach to determine a research question that would enable them to fix their research questions. The target population of this study is medical academics from eleven Malaysian Public Universities. The development and validation of the scale involved six phases that consist of purpose of the scale, define construct, scale development, scale testing and Rasch analysis. Three main dimensions generated from the main elements of BDI model and IBM that explain the formation or underlying structure conception of intention. Items clarity is aligned with the scale’s purpose, research framework and theoretical construct. The items of Intention to Stay Scale (ITSS) also have adequate fit statistics, displaying that each item relates to the variable and measurement tool in a meaningful way. The person-item distribution for ITSS is well targeted, and the scale has high item reliability which shows that the item adequacy to measure what should be measured and demonstrate high separation. The scale also has met the expectations of the Rasch model for unidimensionality and the items adequately represent the construct and make sense as a “ruler”. ITSS is unbiased between genders and able to create valid inference regarding the intention of current medical academics to stay in Malaysian public universities.